RISK OF CARDIOVASCULAR DISORDER IN HIV PATIENTS IN INDONESIA: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.67 - Ismail - Fahmi (International Journal of Nursing and Health Services (IJNHS), 2019)
Abstract HIV is a major health problem in the world. HIV infection has the effect of reducing immunity status and increasing the risk of cardiovascular disease. Antiretroviral (ART) use as a therapy for HIV also increases the risk of heart disease. Objective: This literature review aims to identify the risk of cardiovascular disorders in HIV patients in Indonesia. Method: literature review of articles published January 2009 to September 2018 using search keywords namely 'Anti-retroviral therapy', 'Cardiovascular disease', 'Corronary artery disease', and 'HIV'. Results: There were 21 journal articles that were relevant to the design and purpose of paper and 3 articles that discussed the risk of heart disease in HIV patients in Indonesia. The results of the literature review showed that HIV patients in Indonesia are at risk of developing cardiovascular disorders which are exacerbated by the use of ART and smoking behavior. The risk of cardiovascular disease includes structural abnormalities and coronary heart disease. Conclusion: HIV patients have a high risk of developing cardiovascular disease. This is a challenge for health workers, the government and researchers, to develop appropriate strategies and methods in reducing the risk of cardiovascular disorders especially in low-middle income country countries such as Indonesia. Keyword: Anti-retroviral therapy, cardiovascular disease, HIV, AIDS, HIV in Indonesia